[East Indian girl in a garden] - (:unkn) unknown (My University, 2008)
Photo of a young East Indian girl wearing a simple orni on her head, a bodice and skirt and bangles or bracelets on her arms.
Colour: Black and White; Style: Portrait; Other: Bordered, Divided
Keywords: Postcards; Women, East Indian--Caribbean Area; Ethnic costume--India; Young women--Caribbean Area; Jewelry--India